Training and decolonial practices of teachers who are trainers: against the established - Nascimento de Mattos, Sandra Maria (2021)
This article aims to present decolonial teaching practices of teacher educators who transgress what is instituted in their classrooms. These practices involve the cultural encounter with its varied possibilities to promote the teaching and meaningful learning of students. Initial and continuing education participates in this change in perspective and directly influences teaching practice, when these teachers, future or active, acquire knowledge about certain ways, such as ethnomathematics, to assist their teaching practice. It is the development, in a way, of creative insubordination, ways of insurgencies that contribute to reflect on the structuring of the coloniality of power, being and knowledge. The methodology used was an ethnographic type with immersion in locus and conversation circles, resulting in enriching experiences. The research shows that diversified teaching strategies promote more effective learning and modify the performance of teachers.